The nexus between Public Investment Fund Sports Revenue and economic development in Saudi Arabia - Almdoudi, Furqan Mahfouz Ali; Alalmai, Somaiyah Fahad (Journal of Economic, Administrative and Legal Sciences, 2025)
This research is targeted at analyzing the possible impacts of sports investment and sports events. This study discusses the multi-dimensional influences of the Kingdom of Saudi Arabia (PIF) activities concerning sports event sponsorship on tourism revenue, GDP Growth Rate, Foreign direct investment inflows (FDI), and economic diversification. The study employs the “Multiple linear regression model” for data analysis. The analysis is based on secondary data, and the sample incorporates annual time series information covering the period between 2018 to 2023. The results reveal that the coefficient for GDP Growth Rate is statistically significant, while, the coefficients of FDI and Tourism Revenue are not statistically significant at the conventional level. The results indicate that the sports industry positively impacts economic activity. Based on empirical analysis, Saudi Arabia must continue hosting mega-events to support the Vision 2030 plan to diversify the Saudi economy. the paper is intended to give information on the economic landscape of Saudi Arabia and global image production in sports event sponsorships.